(untitled) (Journal of Medical & Health Sciences Review, 2025)
OBJECTIVE: To compare the mean pruritus score on VAS at the last visit before presentation for delivery in ursodeoxycholic acid versus placebo groups for the management of pregnant women with intrahepatic cholestasis. METHODS: The study design was a randomized controlled trial, to compare the mean pruritus score on VAS at the last visit before presentation for delivery in ursodeoxycholic acid versus placebo groups for management of pregnant women within trahepatic cholestasis. Sample formula and size: 100 (50 in each group). In a study comparing ursodeoxycholic acid versus placebo; post-randomization maternal itch score was lower in the ursodeoxycholic acid group than in the placebo group (49.5+12.9 versus 56.9+13.3; mean difference -5.7 mm [95% CI -9.7 to -1.71], p=0.0054) (10). The sampling technique was non-probability consecutive sampling. Data analysis was performed as, data was entered in and analyzed through SPSS-25. Mean and standard deviation was calculated for age and pruritus on VAS for pruritus assessed before start ofdrug and at last visit before presentation for delivery in both groups. RESULTS: UDCA was accepted well. Compared to moms who did not receive medication, those who received UDCA had an ICP diagnosis five week’s sooner. Total BA and ALT levels were greater in the UDCA-using group at diagnosis than in the non-UDCA-using group. The perinatal outcome was favorable, and the majority of deliveries were induced. The UDCA group had significantly lower Apgar ratings at 5 minutes (p <0.05), however both groups’ fetal umbilical artery pH values were comparable (p >0.05). Those deliveries were induced shortly after diagnosis for 30 patients whose total BA was greater than 40 μmol/l at diagnosis, 24 of whom had UDCA, and 6 of whom were not taking any medication. These patents also had a higher prevalence of premature labor (p<0.05).ICP was identified sooner in women having preterm newborns, and their pruritus had a noticeably earlier beginning. Both at diagnosis and at first control, those pregnancies had significantly higher serum ALT and total BA levels. CONCLUSION: Severe ICP (total BA > 40 μmol/l) was linked to preterm labor; ALT levels were also significantly higher, and ICP was identified sooner (p < 0.05). Preterm newborns’ umbilical artery pH levels were not significantly lower, although their Apgar scores were poorer (p < 0.05). Pregnant women tolerated UDCA nicely. The obstetric result was favourable with low-dose UDCA therapy. Careful obstetrical follow-up is still advised.